Analyzing the household's valuation for the improvement of water quality in Tagum City - Rala, Jayrome E.
This study intended to analyze the households' valuation for the improvement of water quality in Tagum City. Specifically, the study aimed to describe the status of the quality of water in the Poblacion of Tagum City and analyze the factors that might affect the respondents' level of WTP. Stratified random sampling was used in selecting two hundred respondents from the twenty-four Puroks in the Barangay Poblacion of Tagum City. The Contingent Valuation Method was applied using the Willingness to Pay approach to determine the households' valuation for the improvement of water quality. The independent variables included in the study were the respondents' educational attainment, the respondents' gender, the household's monthly income, the household size, the respondents' water quality rating, the household's monthly water consumption (in cubic meters), the household's monthly water bill, the respondents' awareness to diseases, competitive uses of water, the households' domestic uses of water, and the price of bottled water. Among those, only five variables were found to have statistically significant influence on WTP. Those variables were monthly water consumption (in cubic meter), average monthly water bill, respondents' awareness to diseases, respondents' gender, and households' monthly income. The R2 of 0.391 indicates that these five variables accounted for 39.1% of the variations in WTP. Although expenditure for the improvement of the water quality in the city is not yet known, the computed WTP may aid in determining future improvement cost by the local government unit of Tagum City. The result of the study can facilitate the decision making of the local government in assessing the economic value of improving the quality of water in the City.